THE SOCIAL IMPACT OF MICROFINANCE INSTITUTIONS IN EMPOWERING BOTTOM OF THE PYRAMID GROUPS (BoP) (Case Study of Koperasi Kasih Indonesia) - Wahyu Indriyo; Jonathan Gultom (Universitas Agung Podomoro, 2023)
This article aims to analyze the social impact of Koperasi Kasih Indonesia (KKI) as a microfinance institution (MFI) in terms of the benefits received by its members and how to measure them. Conventionally the parameters of range expansion (outreach) in disbursing microcredit are widely used to measure the social impact of MFIs. The more extensive reach also indicates the potential benefits that can be obtained by MFIs. Therefore, if it is separate from the social mission, the target reach will only encourage the commercial motive of the MFI. Measuring the social impact of MFIs takes work and requires more funding. Social Impact Causal Chain model used to see the social impact of KKI on its members. The results found that there are two types of social impacts of KKI, quantitatively and qualitatively. They explain the transformation process of members who originally received benefits more in material form (tangible) to be more immaterial benefits (intangible). The research also found that there are superior KKI factors such as the commitment to the social mission which is implemented in programs innovatively, supported by organizational governance and values instilled in officers and members strongly.